Dieta estacional del Tayassu pecari (Artiodactyla: Tayassuidae) en el Parque Nacional Corcovado, Costa Rica - Altrichter, Mariana (2000)
The diet of the white-lipped peccari Tayassu pecari was studied from July 1996 to April 1997 in Corcovado National Park, Costa Rica, through fecal analysis and direct observations. The feces consisted of 61.6% fruits, 37.5% vegetative parts, 0.4% invertebrates and 0.5% unidentified material. These proportions are similar to those reported for white-lipped peccaries diet in South America, but the species consumed were different. In Corcovado, the white-lipped peccary fed on parts of 57 plant species (37 of them fruits). Moraceae was the most represented farnily. In contrast, the diet of the Peruvian Amazon peccary primarily consists of plant parts (Arecaceae). Costa Rican peccary diet consisted of vegetative parts from Araceae and Heliconaceae. Direct observation showed that peccaries spent 30% of feeding time rooting. Samples taken from rooting sites suggest that peccaries fed on earthworrns. Diet differed between months, seasons and habitats. They ate more fruits in coastal and primary forests and more vegetative parts in secondary foresto In the months Octubrer and November the consumption of vegetative parts excéeded fruit consumption.